Pretreatment of NaCl enhances the drought resistance of cotton by regulating the biosynthesis of carotenoids and abscisic acid - Ni, Kesong; Dai, Maohua; Lu, Xuke; Zhang, Yuexin; Fan, Yapeng; Xu, Nan; Feng, Xixian; Huang, Hui; Wang, Jing; Rui, Cun; Zhang, Hong; Lei, Yuqian; et al. (Frontiers in Environmental Science, 2022)
Drought stress is one of the abiotic stresses that limits crop production and greatly affects crop yield. Enhancement of plant stress resistance by NaCl pretreatment has been reported, but the mechanism by which NaCl pretreatment activates cotton stress resistance remains unclear. In this study, upland cotton (Gossypium hirsutum cv H177) was used as the material to conducted the treatments with three replications: 0 Mm NaCl + 0% PEG6000 (Polyethylene glycol), 0 mM NaCl + 15% PEG6000, 50 mM NaCl + 15% PEG6000 to explore the molecular mechanism by which NaCl improves the drought tolerance of cotton. The results showed that pretreatment with 50 mM NaCl could alleviate the adverse effects of PEG on cotton seeds while promoting the elongation of root length. RNA-seq showed that NaCl specifically induced the expression of carotenoid-related genes. By silencing the upstream gene GHLUT2 of lutein synthesis, it was found that the chlorophyll of silenced plants decreased, and leaf wilting was more sensitive to drought. We found that NaCl enhanced the drought resistance of cotton by regulating genes related to the carotenoid and abscisic acid downstream synthesis pathways. This study provides a new reference for the study of drought resistance in cotton and a theoretical basis for the molecular breeding of cotton.